5-Methyl-2,4-bis(methylsulfanyl)tricyclo[6.2.1.0(2,7)]undeca-4,9-diene-3,6-dione - von Richthofen, Andreas A. (International Union of Crystallography, 2010)

(untitled)
The structure analysis of the title compound, C(14)H(16)O(2)S(2), shows the SMe and H atoms of the bond linking the six-membered rings to be syn and also to be syn to the bridgehead –CH(2)– group. Each of the five-membered rings adopts an envelope conformation at the bridgehead –CH(2)– group. The dione-substituted ring adopts a folded conformation about the 1,4-C⋯C vector, with the ketone groups lying to one side. The cyclohexene ring adopts a boat conformation.